2017
DOI: 10.1097/mcg.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of 3 Bifidobacteria Decreases Abdominal Pain and Improves the Quality of Life in Children With Irritable Bowel Syndrome

Abstract: In children with IBS a mixture of Bifidobacterium infantis M-63, breve M-16V, and longum BB536 is associated with improvement in AP and QoL. These findings were not confirmed in FD subjects. Trial identifier: NCT02566876 (http://www.clinicaltrial.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 37 publications
0
67
0
4
Order By: Relevance
“…The role of probiotics in IBS, not only in symptoms, but also in gut microbial composition improvement, has been investigated in several controlled trials, although many of them were short-term and showed methodologic limitations. [25][26][27][28] To date, the benefit of use of probiotics in IBS is still unproven. Different species, strains, mode of administration and doses of probiotics were used, but it is difficult to define both a specific gut microbial signature in IBS and the optimum probiotic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The role of probiotics in IBS, not only in symptoms, but also in gut microbial composition improvement, has been investigated in several controlled trials, although many of them were short-term and showed methodologic limitations. [25][26][27][28] To date, the benefit of use of probiotics in IBS is still unproven. Different species, strains, mode of administration and doses of probiotics were used, but it is difficult to define both a specific gut microbial signature in IBS and the optimum probiotic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent randomised controlled trials demonstrated no significant benefit of probiotics preparations over placebo in the treatment of pain in adults with IBS44 in contrast to the benefit observed in some (but not all) trials in children with regard to frequency and intensity of abdominal pain, for example, with a combination of three Bifidobacterial species45 or a single bacterial species 46…”
Section: Current Approaches To Manage Visceral Pain In Patients With Ibsmentioning
confidence: 95%
“…Probiotics may be employed under conditions of disorder as well. In patients with IBS (see section below), probiotic intervention has been shown to ameliorate symptoms (e.g., Whorwell et al, 2006), including a reduction of abdominal pain in children (Giannetti et al, 2017). There is some evidence that probiotics can ameliorate anxiety and depressive symptoms (Pirbaglou et al, 2016), although research has been more likely to examine depressive symptoms in volunteers who do not necessarily suffer from clinical depression (Huang, Wang, & Hu, 2016).…”
Section: The Impact Of Psychobioticsmentioning
confidence: 99%